Limitless analytics with Azure Synapse : an end-to-end analytics service for data processing, management, and ingestion for BI and ML requirements /: an end-to-end analytics service for data processing, management, and ingestion for BI and ML requirements. (2021) - Mishra, Prashant Kumar; Kumar, Mukesh
No abstract available